Social psychology - Aronson, Elliot 1932-; Wilson, Timothy D.; Sommers, Samuel R. (Pearson, 2021)
This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. For courses in Social Psychology Make research relevant through a storytelling approach Social Psychology introduces the key concepts of the field through an acclaimed storytelling approach that makes research relevant to students. Drawing upon their extensive experience as researchers and teachers, authors Elliot Aronson, Tim Wilson, and Sam Sommers present the classic studies that ha
Keywords: Sozialpsychologie; Einführung; Lehrbuch